“EMOTIONAL INTELLIGENCE AND SELF-ESTEEM,” POWERS OF MANAGEMENT AND CONTROL OF THE UNIVERSITY - Vásquez Quiroa, Danilo (2011)
The message of this publication is intended to focus and provide an integrative concept of scenario that college students must meet to become graduates and professional circumstances that they must live environment, but nature can cause feelings of tension, also means of overcoming existing installed on the same human nature. For which definitions and classifications are presented and investigated by the appropriate specialists, plus the address of the author who fully intend to capitalize on subliminal for university professionals contribute to humanity’s intellectual capital, in an effort to correct to some extent the efforts than previous generations of professionals and businessmen, have damaged the ecological environment, economic, but mainly the environment of the realm of attitudes on global society.